Pendampingan Revitalisasi Alat dan Mesin Pengolahan Kopi di Desa Karang Sidemen Kecamatan Batukliang Utara Kabupaten Lombok Tengah - khalil, Fakhrul Irfan; Amuddin; Ida Ayu Widhiantari; Isnaini Puspitasari; Wahyudi Zulfikar; Rosyid Ridho (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Karang Sidemen Village, located in North Batukliang District, Central Lombok Regency, has significant potential as a center for high-quality coffee production in Lombok. The village directly borders several forest areas, including Tahura Nuraksa, Community Forest (HKm), Hortipark, and the Rarung Special Purpose Forest Area (KHDK). This availability of resources has led 75% of the community to manage a highly regarded and popular commodity, namely Robusta coffee. Numerous Women’s Farmer Groups and MSMEs manage coffee as a flagship product. Additionally, the village has several attractive locations as tourist destinations. However, this potential has not been fully optimized due to a lack of knowledge and education among farmers and the local community. One factor affecting coffee quality is the equipment and machinery used in the production process. Farmers’ knowledge in operating equipment, maintenance, and proper safety techniques is still not optimal. This is evidenced by the many machines and equipment that are not used in production houses. To address this condition, initiatives are needed to conduct outreach and mentoring activities from academics and practitioners that are inclusive, embracing the entire community. Through outreach sessions, farmers and the local community will be given a deep understanding of the technical operation of coffee processing equipment and machinery. Maintenance techniques and usage according to standard procedures will also be covered. Practical training sessions will enable farmers to improve their skills, ensuring that each stage of equipment and machinery use is carried out correctly, systematically, and with an understanding of basic Occupational Health and Safety (OHS) concepts. By applying the best practices obtained through these outreach and training sessions, farmer groups in Karang Sidemen Village are expected to further improve the quality and quantity of production. This will not only provide direct benefits to farmers but also enhance the competitiveness of the village’s coffee products in both local and international markets. With the support and revitalization of existing equipment and machinery, the local community is expected to become agents of change to achieve higher quality standards, realizing the potential of Karang Sidemen Village’s local coffee.